Budget performance in public and private universities in Colombia (2013)
Education in Colombia in the light of the Constitution constitutes a right for citizens and a duty to the state, which is why it is considered as a central objective of social and economic development, The education is the by all means not just the human resource but also how the society becomes. Higher education in Colombia has a mixed offer we have public and private IES, coverage is divided into 50% for each, the financing system of private universities is given by the income received for tuition, based on this income structure their budget and project development, for public universities revenues correspond to contributions from the State governed by law 30 of 1992, given the transformation that has taken education in the last 20 years the budget provided is insufficient.